Optimasi Penghilangan COD dan Warna dengan Proses Koagulasi, Flokulasi dan Sedimentasi untuk Pengolahan Air Limbah Industri Kertas - Ulung Muhammad Sutopo; Elfia Fariza; Lastri Sartika; Reni Desmiarti (Politeknik ATI Padang, 2025)
Pulp and paper industry wastewater contains very potential pollutants, especially suspended solids, BOD, and COD which are stable colloids and difficult to separate. To reduce the COD content in paper industry wastewater, the addition of coagulant chemicals is needed. The coagulant used is 20% poly aluminum chloride (PAC) with a variation of 100-600 mg/L and polymer with a dose of 1-6 mg/L to reduce COD and color in wastewater treatment. The settling time used is 1-25 minutes. The effect of adding PAC coagulant is able to reduce COD and color of wastewater at the optimal point, but when the addition of PAC is excessive, the COD and color of the wastewater increase again. The results found that the optimum conditions occurred at a PAC dosage of 400 mg/L and a polymer dosage of 4 mg/L with a settling time of 20 minutes, resulting in a reduction of TSS, COD, and color to 12 mg/L, 102 mg/L, and 123 PtCo, respectively. The combination of coagulation-flocculation-sedimentation processes under these optimum conditions proved effective as a tertiary treatment to meet wastewater quality standards for the paper industry